The degradation behavior of nanoscale HA/PLGA and α-TCP/PLGA composites. Issue 2 (June 2014) - Ege, Duygu; Cameron, Ruth; Best, Serena
Abstract : The aim of this work was to prepare and analyze the degradation properties of pure PLGA, homogeneous α-tricalcium phosphate ( α -TCP)/PLGA and hydroxyapatite (HA)/PLGA composites for potential bone replacement applications. α -TCP and HA powders were prepared in-house and 25 nominal wt% of calcium phosphate (CaP) powder was incorporated into commercially available PLGA pellets by twin screw extrusion. The degradation studies showed that pure PLGA had the fastest degradation rate followed by HA/PLGA and α -TCP/PLGA. Overall, it was found that α -TCP acted as a better buffering agent than HA, resulting in reduced acid group autocatalysis and hence a slower degradation rate.